Molecular evolution of gustatory receptors in the Anopheles gambiae complex - Zachary R. Popkin-Hall; Michel A. Slotman (BMC Ecology and Evolution)
Abstract Background Mosquitoes in the Anopheles (An.) gambiae species complex are major vectors of Plasmodium falciparum malaria. One reason for this is the high anthropophily of the constituent species An. coluzzii, An. gambiae sensu stricto, and An. arabiensis. In contrast, their sister species An. quadriannulatus is highly zoophilic. Anopheles mosquitoes largely rely on chemical cues for host-seeking, which are primarily detected by four chemosensory gene families: olfactory receptors (Ors), ionotropic receptors (Irs), gustatory receptors (Grs), and odorant binding proteins (Obps). Genes from these families that have been implicated in host adaptation show evidence of positive selection in other insect species, including other mosquitoes. As such, we analyzed the molecular evolutionary patterns of the gustatory receptors within the Anopheles gambiae complex, with a particular interest in identifying Grs that show evidence of positive selection in highly anthropophilic species. Results We identified sixteen Grs that show evidence of potential positive selection using the McDonald-Kreitman test, including four putative sugar receptors and two Grs with unknown ligands that are relatively highly expressed in chemosensory organs of either An. coluzzii or An. quadriannulatus. In addition, we identified twelve Grs that show evidence of potential purifying selection using the McDonald-Kreitman test, and twelve Grs that may have experienced a selective sweep using the DH test, including three putative sugar receptors and the carbon dioxide receptor Gr24. We also identified both positive and purifying selection in the coastal species An. melas (West Africa) and An. merus (East Africa). Conclusions Our results, together with transcriptomic data, identify four Grs as possible candidates for involvement in the evolution of vertebrate host preference in the An. gambiae complex, as may have occurred in the An. farauti complex. They also point to sugar receptors as playing a role in recent adaptation of some of these species. As the vast majority of Grs have unknown functions and much is still unknown about the role of Grs in these species, a more complete interpretation of our data necessitates further characterization of these genes.